2013
DOI: 10.1007/s00167-013-2632-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of custom to standard TKA instrumentation with computed tomography

Abstract: When evaluated with CT, custom instrumentation performs similar or better to standard instrumentation in component alignment and accurately templates component size. Tourniquet time was mildly increased for custom compared to standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…In accord with earlier studies, we would argue that the use of a unisex prosthesis to recreate posterior condylar anatomy is likely sufficient [22]. Other custom implants have attempted to account for differences in PCO by varying the size of medial and lateral posterior condyles; most authors agree that more longterm follow-up is needed to determine the potential benefits of such systems [28][29][30]. However, in light of the differences discussed above, TKA designs should consider including a more posteriorly offset medial posterior condyle to address this known osteological difference.…”
Section: Medial Lateralsupporting
confidence: 57%
“…In accord with earlier studies, we would argue that the use of a unisex prosthesis to recreate posterior condylar anatomy is likely sufficient [22]. Other custom implants have attempted to account for differences in PCO by varying the size of medial and lateral posterior condyles; most authors agree that more longterm follow-up is needed to determine the potential benefits of such systems [28][29][30]. However, in light of the differences discussed above, TKA designs should consider including a more posteriorly offset medial posterior condyle to address this known osteological difference.…”
Section: Medial Lateralsupporting
confidence: 57%
“…Most of the outcomes are comparable, however, 2 articles published significant better outcome with extramedular rods [25,26] . Only Ng et al [22] found significant better outcome with MRI based PSG for the tibia. LevelⅠ results are very remarkable in regard to the LTC.…”
Section: Discussionmentioning
confidence: 96%
“…This perioperative guiding technique eliminates the use of intra-and extra medullar rods to make bony resections. Previous published results on PSG suggest this to be a good alternative to conventional instrumentation with comparable results, improved radiological outcome and reduced operation time and blood loss [7,[13][14][15][16][17][18][19][20][21][22][23] . This prospective study on PSG between different manufacturers and conventional technique for the implantation of TKA was designed to address the following research questions: Is there a significant difference in outliers in alignment in the frontal and lateral plane between PSG and conventional TKA, secondly between the four individual different PSG systems and thirdly between cut-and pin PSG?…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations